2018 IEEE International Conference on Big Data (Big Data) 2018
DOI: 10.1109/bigdata.2018.8621922
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Malicious Insider Threat Scenarios Using Organizational Data and a Heterogeneous Stack-Classifier

Abstract: Insider threats continue to present a major challenge for the information security community. Despite constant research taking place in this area; a substantial gap still exists between the requirements of this community and the solutions that are currently available. This paper uses the CERT dataset r4.2 along with a series of machine learning classifiers to predict the occurrence of a particular malicious insider threat scenario -the uploading sensitive information to wiki leaks before leaving the organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Table 12 displays the performance of the proposed method compared to existing approaches. Our proposed model demonstrates a clear advantage in the detection performance when compared to other works in the literature for insider threat detection utilizing the CERT r4.2 dataset [73][74][75][76][77][78][79][80][81][82]. The superior detection results are achieved by [80] utilizing HMM and by our work utilizing DT + SMOTE and RF + SMOTE methods with an AUC-ROC value of 1.0, outperforming other previous works.…”
Section: Approachmentioning
confidence: 67%
See 1 more Smart Citation
“…Table 12 displays the performance of the proposed method compared to existing approaches. Our proposed model demonstrates a clear advantage in the detection performance when compared to other works in the literature for insider threat detection utilizing the CERT r4.2 dataset [73][74][75][76][77][78][79][80][81][82]. The superior detection results are achieved by [80] utilizing HMM and by our work utilizing DT + SMOTE and RF + SMOTE methods with an AUC-ROC value of 1.0, outperforming other previous works.…”
Section: Approachmentioning
confidence: 67%
“…The least detection result is achieved when applying the LR + SMOTE method with an AUC-ROC value of 0.79. It is observed that several works achieved excellent results with AUC-ROC values of 0.98 and 0.99 utilizing different methods such as in [75,79] and [82]. Our proposed approach achieved an improved AUC-ROC curve value of 1.0 when applying DT+ SMOTE and RF + SMOTE methods.…”
Section: Approachmentioning
confidence: 74%
“…Hsieh et al, Isis Rose et al, and Nkosi et al [93][94][95] analyzed active directory services and audit logs using the Markov model, hierarchical task decomposition, and a rule learning algorithm, respectively. The works [96][97][98][99][100][101][102][103][104][105][106][107][108][109] combined and analyzed multiple log features collected from multiple sources, such as email, HTTP, logon, files, and devices to detect insider threats using statistical methods and machine-learning techniques.…”
Section: Cyber Activity Behaviormentioning
confidence: 99%
“…[ 35,45,[62][63][64][65][66][67][68]97,101,105,106,110,112,117,121,124,131,133,182,194] Time complexity…”
Section: Roc or Aucmentioning
confidence: 99%
“…Honeypots can operate both internally and externally to lure in attackers. By operating internally they can collect data from an internal threat actor, such as insider threats [ 5 , 6 ]. They can also collect data from external threat actors by attracting them towards their open and poorly secured ports.…”
Section: Introductionmentioning
confidence: 99%